2020
DOI: 10.25259/sni_282_2020
|View full text |Cite
|
Sign up to set email alerts
|

Cranial angiomatoid fibrous histiocytoma: A case report and review of literature

Abstract: Background: Angiomatoid fibrous histiocytoma (AFH) is a rare low-grade soft-tissue tumor that typically arises from the deep dermal and subcutaneous tissue of the extremities in children and young adults. Intracranial AFH is exceedingly rare, and only four cases of primary AFH tumors have been reported to date. Case Description: A 43-year-old male presented to our hospital with headaches, vision changes, and a known brain tumor suspected to be an atypical meningioma. After undergoing craniotomy for resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…More than 90% of CCS tumors harbor an EWSR1:ATF1 fusion, whereas CREB1 and CREM tumors have been, respectively, rare and only exceptionally described ( 19 ). The recent literature identified a novel intracranial histomolecular entity, variably referred to as the intracranial myxoid mesenchymal tumor (IMMT) or the intracranial AFH (44 reported cases to date) ( 16 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ). In the CNS, because these tumors mostly lacked the characteristically histopathological triad of typical AFH of the soft tissue and because they often presented a myxoid stroma, the terminology “intracranial myxoid mesenchymal tumor” has been preferred by some authors ( 21 , 22 , 25 , 27 , 30 , 31 , 33 , 36 , 39 , 40 , 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of CCS tumors harbor an EWSR1:ATF1 fusion, whereas CREB1 and CREM tumors have been, respectively, rare and only exceptionally described ( 19 ). The recent literature identified a novel intracranial histomolecular entity, variably referred to as the intracranial myxoid mesenchymal tumor (IMMT) or the intracranial AFH (44 reported cases to date) ( 16 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ). In the CNS, because these tumors mostly lacked the characteristically histopathological triad of typical AFH of the soft tissue and because they often presented a myxoid stroma, the terminology “intracranial myxoid mesenchymal tumor” has been preferred by some authors ( 21 , 22 , 25 , 27 , 30 , 31 , 33 , 36 , 39 , 40 , 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the vast majority of intracranial mesenchymal tumors with FET:CREB fusions were reported to be negative for cytokeratin. 3,4,10,14,[16][17][18]21,27 However, a few recent studies showed that a small subset of these tumors were positive for cytokeratin, 19,28,29 indicating that cytokeratin expression does not necessarily exclude the diagnosis of IMMT/intracranial AFH. Furthermore, we investigated the cytokeratin subtypes expressed in the present tumor and found diffuse staining for CK8/18.…”
Section: Discussionmentioning
confidence: 99%
“…EWSR1 is a hybrid gene involved in multiple tumor gene translocations, which are translocated and fused with multiple partner genes, indicating that tumors have different speci c morphologies. Gene fusion of the EWSR1 and CREB family genes (CREB1, ATF1, and CREM) is a newly discovered translocation fusion event that includes soft tissue clear cell sarcoma (mainly EWSR1-ATF1 fusion), 2 malignant gastrointestinal neuroectodermal sarcoma (mainly EWSR1-CREB1 fusion), 2 angiomatoid brous histiocytoma (mainly EWSR1-ATF1 fusion), 3 and head and neck clear cell carcinoma (EWSR1-ATF1 fusion). The fusion of different partners indicates that these sarcomas have signi cant heterogeneity in morphology, immunophenotype, and behavior, ranging from low-level inertia (such as angiomatoid brous histiocytoma) to high invasiveness.…”
Section: Introductionmentioning
confidence: 99%